Sistem Penghantaran Nanostructured Lipid Carrier (NLC) Mengandung Senyawa Antioksidan - N. Resa Nurul Pazrian; Hanifa Rahma; Gita Cahya Eka Darma (UNISBA Press, 2024)
Abstract. Free radicals are unstable atoms or molecules with a high level of reactivity caused by the existence of one or more unpaired electrons in their outermost structure. Antioxidants are required to reduce free radical activity because antioxidant compounds can donate electrons to stabilise free radicals. However, because antioxidants are rapidly hydrolyzed and have low stability, the use of the relatively new